2022
DOI: 10.3390/molecules27061875
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintic Effect of Leucaena leucocephala Extract and Its Active Compound, Mimosine, on Vital Behavioral Activities in Caenorhabditis elegans

Abstract: Helminth infections continue to be a neglected global threat in tropical regions, and there have been growing cases of anthelmintic resistance reported towards the existing anthelmintic drugs. Thus, the search for a novel anthelmintic agent has been increasing, especially those derived from plants. Leucaena leucocephala (LL) is a leguminous plant that is known to have several pharmacological activities, including anthelmintic activity. It is widely known to contain a toxic compound called mimosine, which we be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 84 publications
(116 reference statements)
0
4
0
Order By: Relevance
“…For example, syringaresinol is a lignan with anti‐inflammatory activity (Bajpai et al, 2018). Mimosine is a tyrosine analog with a variety of biological properties, including anti‐inflammatory, antidisease, and anticancer properties (Widaad et al, 2022). Cadabicine mainly exists in capers ( Capparis spinosa ) and Cadaba farinosa Forssk, and related medical studies have shown that cadabicine can alleviate pain by inhibiting the activity of enkephalinase (Annaz et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, syringaresinol is a lignan with anti‐inflammatory activity (Bajpai et al, 2018). Mimosine is a tyrosine analog with a variety of biological properties, including anti‐inflammatory, antidisease, and anticancer properties (Widaad et al, 2022). Cadabicine mainly exists in capers ( Capparis spinosa ) and Cadaba farinosa Forssk, and related medical studies have shown that cadabicine can alleviate pain by inhibiting the activity of enkephalinase (Annaz et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…For example, syringaresinol is a lignan with anti-inflammatory activity (Bajpai et al, 2018). Mimosine is a tyrosine analog with a variety of biological properties, including antiinflammatory, antidisease, and anticancer properties (Widaad et al, 2022). Cadabicine mainly exists in capers (Capparis spinosa) and…”
Section: Identification Of Antagonistic Fungimentioning
confidence: 99%
“…Linoleic acid (1) Seeds, mature pods, immature pods Pheophytin-a (2) Leaves Pheophorbide a methyl ester (3) Leaves, immature pods 13 2 -hydroxy-(13 2 -S)-pheophytin a (4) Leaves Aristophyll-C (5) Leaves Methyl-13 2 -hydroxy-(13 2 -S)-pheophorbide b (6) Leaves 5α, 8α-epidioxy-(24ξ)-ergosta-6, 22-dien-3β-ol (7) Mature pods β-sitosterol (8) Seeds Lupeol (9) Mature pods β-sitostenone (10) Mature pods Ficaprenol-11 (11) Immature pods Squalene (12) Immature pods Cis-coumaric acid (13) Immature pods Trans-coumaric acid (14) Immature pods Pyropheophorbide a (15) Immature pods 1, 3-Dipalmitoyl-2-oleoylglycerol (16) Mature pods, immature pods…”
Section: Compounds Partsmentioning
confidence: 99%
“…The leaves and fruits of L. leucocephala contain phytoalkaloids, and the leaves of L. leucocephala contain toxic mimosine (Mimosine, b-[N-(3-hydroxy-4-pyridone)]-a-aminopropionicacid) and poison phenol compounds, such as acids and flavonoids [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%